Mining Service Quality Dimensions from User-Generated Content : A Case Study on Chinese Fresh Food E-Commerce - Xiaomei, Han; Hamrila, Abdul Latif; Chin Hong, Puah (Macrothink Institute, USA, 2026)
This study explores the key dimensions of service quality in China’s fresh food e-commerce sector by analyzing large-scale user-generated content (UGC) from four major platforms. Employing the BERTopic model, the research extracted 18 latent topics from 56,765 customer reviews, which were further mapped into six overarching service quality dimensions: Product Quality, Logistics & Cold Chain, Economic Efficiency, Customer Service, Platform Experience, and Packaging & Hygiene. These dimensions reflect both classical service constructs from SERVQUAL and E-S-QUAL frameworks and unique operational characteristics specific to fresh e-commerce, such as perishability and cold-chain logistics. The study demonstrates the effectiveness of topic modeling in capturing authentic consumer perceptions and offers a more context-sensitive framework for service evaluation. The findings provide theoretical contributions by refining existing models and offer actionable insights for platform operators to optimize service design, enhance customer satisfaction, and improve competitive advantage in China’s evolving digital marketplace.